Innovations in enterprise information systems management and engineering : 4th International Conference, ERP Future 2015 - Research, Munich, Germany, November 16-17, 2015 /: 4th International Conference, ERP Future 2015 - Research, Munich, Germany, November 16-17, 2015. (2016) - Unknown
No abstract available